2018
DOI: 10.1590/1516-3180.2017.0362080218
|View full text |Cite
|
Sign up to set email alerts
|

Coarse particles and hospital admissions due to respiratory diseases in children. An ecological time series study

Abstract: This study showed the impact of coarse-fraction exposure on hospital admissions among children due to respiratory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…Associations between mortality and levels of CO, SO 2 , and, to a lesser extent, PM 10 were observed in São Paulo, for associations between mortality in elderly people and air pollution, using Generalized Additive Models (GAM) [32]. Other research has shown the impact of coarse-fraction exposure on hospital admissions among children due to respiratory diseases, where an increase of 5 μg/m 3 in the coarse fraction concentration implied an increase in the relative risk of hospitalizations of up to 4.8% [33]. Another study was carried out using daily time-series from hospitalization and pollutant data in Vitoria, ES, Southeastern Brazil, from 2001 to 2006 showing that for an increment of 10 µg/m 3 of the pollutants PM 10 , SO 2 , and O 3 , the percentage of relative risk (%RR) for hospitalizations due to total respiratory diseases increased by 9.6, 6.9, and 1.9, respectively [34].…”
Section: Discussionmentioning
confidence: 99%
“…Associations between mortality and levels of CO, SO 2 , and, to a lesser extent, PM 10 were observed in São Paulo, for associations between mortality in elderly people and air pollution, using Generalized Additive Models (GAM) [32]. Other research has shown the impact of coarse-fraction exposure on hospital admissions among children due to respiratory diseases, where an increase of 5 μg/m 3 in the coarse fraction concentration implied an increase in the relative risk of hospitalizations of up to 4.8% [33]. Another study was carried out using daily time-series from hospitalization and pollutant data in Vitoria, ES, Southeastern Brazil, from 2001 to 2006 showing that for an increment of 10 µg/m 3 of the pollutants PM 10 , SO 2 , and O 3 , the percentage of relative risk (%RR) for hospitalizations due to total respiratory diseases increased by 9.6, 6.9, and 1.9, respectively [34].…”
Section: Discussionmentioning
confidence: 99%
“…A metodologia escolhida consiste na revisão da literatura relativa às questões de gênero e sexualidade no âmbito educacional, dialogando com autores como Judith Butler (2018), Sarah Salih (2012), Richard Miskolci (2015), Guacira Lopes Louro (2018), Deborah Britzman (2018) e Mailsa Passos e Rita Pereira (2011). Em conjunto com a análise de conteúdo da capa do capítulo 2, intitulado "Normal", da HQ Bendita Cura -Volume 1, de Mário César (2018). Assim, este trabalho busca refletir, discutir e descrever o sistema de normalização social dentro das instituições de ensino e o processo de silenciamento dos sujeitos que se "desviam" da norma cishéterossexual.…”
Section: Metodologiaunclassified
“…Três pesquisas originais e uma revisão sistemática destacaram as seguintes limitações metodológicas: subnotificação de transtornos respiratórios por limita-ção dos sistemas de informação erro diagnóstico ou na seleção da classificação de doenças, monitoramento de poluentes ambientais, exclusão de tratamentos ambulatoriais 45,49 ou nos sintomas subclínicos quando não investigados 52 .…”
Section: Discussão Modelo Epidemiológico: Explicação Centrada Na Cond...unclassified